2003
DOI: 10.1677/joe.0.1770445
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 11beta-hydroxysteroid dehydrogenases in bovine follicle and corpus luteum

Abstract: In glucocorticoid target organs, local concentrations of active glucocorticoid are determined by the relative expression of two 11 -hydroxysteroid dehydrogenases (HSDs): bi-directional 11 -HSD type1 (11HSD1) that mainly activates cortisone to cortisol, and dehydrogenase 11 -HSD type2 (11HSD2) that inactivates cortisol to cortisone. In this study, we examined the expression of mRNA encoding these two 11 -HSDs in bovine granulosa cells harvested from preovulatory follicles and corpora lutea (CL). Ovaries were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
7
31
0
2
Order By: Relevance
“…Previous studies of 11bHSD in the bovine ovary have been confined to studies of mRNA expression (Tetsuka et al 2003). This study is the first to document changes in enzyme protein expression and cofactor-dependent enzyme activities across the bovine ovarian cycle in granulosa cells and the early CL.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies of 11bHSD in the bovine ovary have been confined to studies of mRNA expression (Tetsuka et al 2003). This study is the first to document changes in enzyme protein expression and cofactor-dependent enzyme activities across the bovine ovarian cycle in granulosa cells and the early CL.…”
Section: Discussionmentioning
confidence: 94%
“…In each case, follicular fluid was aspirated from the ovarian follicles and visually assessed for opacity before being discarded. In light of Tetsuka's prior data (Tetsuka et al 2003), only those follicles that were assessed as healthy by visual inspection (i.e. wellvascularised follicles showing no evidence of collapse or leakage and having clear follicular fluid) were used in this study.…”
Section: Isolation Of Granulosa and Luteal Cells From The Bovine Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…Access of GCs to GC receptors in target tissues is regulated by two 11β-HSDs, bidirectional 11β-HSD type 1 (11β-HSD1) that mainly converts cortisone to active cortisol [11] and 11β-HSD type 2 (11β-HSD2) that inactivates cortisol to cortisone [12]. Although both 11β-HSDs and GC receptors are expressed in the bovine corpus luteum (CL) [13,14] and endometrium [8] throughout the estrous cycle and early pregnancy [15], the role of GC in regulating CL function is still controversial.Our previous in vitro studies have suggested that cortisol suppresses tumor necrosis factor α (TNFα)-stimulated prostaglandin (PG) F 2α production in endometrial stromal cells [8] and inhibits apoptosis of cultured luteal cells induced by TNFα and interferon-γ (IFNG) [13]. Based on the results of in vitro studies, it seems that cortisol plays a role in preventing excessive uterine PGF 2α production and protecting the CL against apoptosis in nonpregnant cattle [13,16].…”
mentioning
confidence: 99%
“…Access of GCs to GC receptors in target tissues is regulated by two 11β-HSDs, bidirectional 11β-HSD type 1 (11β-HSD1) that mainly converts cortisone to active cortisol [11] and 11β-HSD type 2 (11β-HSD2) that inactivates cortisol to cortisone [12]. Although both 11β-HSDs and GC receptors are expressed in the bovine corpus luteum (CL) [13,14] and endometrium [8] throughout the estrous cycle and early pregnancy [15], the role of GC in regulating CL function is still controversial.…”
mentioning
confidence: 99%